Analysis of Factors That Play a Role in the Length of Treatment in Hyperemesis Gravidarum Patients at Raja Ahmad Tabib General Hospital Tanjungpinang, Indonesia - Radhia, Mekar Zenni; Zaini S., Hanifa; Yuliana (Archives of The Medicine and Case Reports, 2024)
Hyperemesis gravidarum (HG) is a pregnancy complication characterized by excessive nausea and vomiting, which can cause dehydration, electrolyte balance disorders and weight loss. The length of stay for HG patients in hospital can vary. This study aims to analyze the factors that contribute to the length of treatment for HG patients at Raja Ahmad Tabib General Hospital Tanjungpinang, Indonesia. This research was conducted with an analytical observational design with a retrospective approach. Data was collected from medical records of HG patients treated at Raja Ahmad Tabib General Hospital Tanjungpinang in the period January 2020 to December 2022. This was done using multiple linear regression. The dependent variable is length of treatment (days). The independent variables analyzed were maternal age, parity, severity of HG, nutritional status, and accompanying complications. A total of 100 HG patients were included in this study. The average length of treatment is 3.5 days. The results of the analysis showed that the factors that contributed to the length of treatment for HG patients were maternal age (p=0.02), parity (p=0.04), and severity of HG (p=0.001). Maternal age, parity, and severity of HG are factors that contribute to the length of treatment for HG patients at Raja Ahmad Tabib General Hospital Tanjungpinang.